Direct Liquid Injection − Low Pressure Chemical Vapor Deposition of Silica Thin Films from Di‐t‐butoxydiacetoxysilane. Issue 12 (17th July 2017) - Vervaele, Mattias; De Roo, Bert; Debehets, Jolien; Sousa, Marilyne; Zhang, Luman; Van Bilzen, Bart; Seré, Stephanie; Guillon, Herve; Rajala, Markku; Won Seo, Jin; Locquet, Jean‐Pierre
Abstract : In this work, an unusual silicon chemical vapor deposition precursor is used, which allows the safe deposition of thin silica films in a controlled and reproducible manner at a lower thermal budget with a newly developed direct liquid injection − low pressure chemical vapor deposition system. The deposition is controlled by parameters such as deposition temperature, partial pressure of the gases, and flow rate of the precursor solution. X‐ray reflectivity and spectroscopic ellipsometry of the deposited samples show that the thickness of the layers is well controlled by deposition temperature, time, and oxygen flow. A growth rate of 4.5 Å min −1 is obtained without the addition of oxygen, which can be increased to 10.2 Å min −1 by the addition of oxygen. Atomic force microscopy, Rutherford backscattering spectroscopy, Fourier transform infrared spectroscopy, and drop shape analysis are used to measure roughness, composition, and hydrophobicity. Thin films of silicon dioxide are successfully grown. In addition, this newly developed system can be used for a wide range of films by varying the precursors or by co‐injecting nanoparticles suspension mixed with the chemical vapor deposition precursor in the direct liquid injection vaporizer. Abstract : This work describes the use of the unusual silicon chemical vapor deposition precursor di‐t‐butoxydiacetoxysilane (DADBS), which allows the safe deposition of thin silica films in a controlled and reproducible manner at a lower thermal budget with a newly developed direct liquid injection – low pressure chemical vapor deposition system.